Performance Measurement Analysis Of Pt Pijar Sukma Using Performance Prism, Analytical Hierarchy Process (Ahp), And Objective Matrix (Omax) Methods - Afifah Afifah; Akhmad Syakhroni; Nuzulia Khoiriyah (Universitas Islam Sultan Agung, 2022)
Abstrack - PT. Pijar Sukma is a furniture industry company, located in Jepara, Central Java. PT. Pijar Sukma is having problems that customer order requests cannot be fulfilled according to production targets. So companies need tools that can measure performance. This research uses the performance prism method which involves stakeholders so that they can form the sides of the prism, namely satisfaction, contribution, strategy, process, and capability. From these methods used to compile key performance indicators (KPIs), 30 KPIs were produced based on satisfaction and contributions in the design that had been prepared, there were 10 strategic KPIs, 10 process KPIs, and 10 capability KPIs that were weighted through the analytical hierarchy process (AHP) method, then scored using the analytical hierarchy process (AHP) method. OMAX to provide an actual value with a score of 1-10 on each KPI and the traffic light system as a color assignment, namely green means very good / the target is maximally appropriate, yellow is quite good / the target has not reached the maximum, and red means bad / the target has not been maximized . The results of the processing and calculation show that the company's performance index value of 2.836 is categorized as red with an actual value of 3.00, meaning the company has achieved the performance measurement plan but has not reached the set target so that the company can maintain good performance and make changes to poor performance by improving performance in red. Key words: Key Performance Indicators (KPI), Performance Prism, Analytical Hierarchy Process (AHP), Objective Matrix (OMAX), and Traffic Light System.